FIQH AL-HADITS: - Ikromi, Zul (Al-Bukhari : Jurnal Ilmu Hadis, 2020)
The trend of  interpretations on Islamic texts from the Qur?an and hadiths has been increasing at the present time. but these understandings leading up to create polemics in the community. The case triggered by some religious circles who  at the end explained religious sources with some limitations, either caused by insufficient understandings or misleadings in interpreting the refferences.  This paper aims to reveal the appropriate method of understanding hadiths which is closer to the intention of the Speaker, due to the fact that there has been a very long time interval between us - as recipients of the  information - with the owner of the text. The research also investigates the language used and the background situations of the hadiths. Therefore, an apppropriate methodological perspective is pivotal to understand the hadiths more comprehensively. This paper is a library research advantaging primarily from the book of  fiqh al-Hadith using content analyses approach. The aim is to find out  appropriate methods or formulas in understanding the traditions of the Prophet Muhammad to bring the prophetic messages for bettter understandings and practices.